An Empirical Analysis on Bank Income Structure and Risk : Evidence in ASEAN-5 countries - Ong, Beatrix Ai Ying (2011)
In the recent decade, non-interest income has grown to be a crucial part of banks’ operating income. Typically, banks are often involved in commission and fee generating activities as well as trading and derivative activities, in their bid to diversify. In general, the industry believes that a higher composition of non-interest incomes to operating incomes will not only increase profitability but also serve to reduce banks’ risk. In opposing strand of literature, it is said that the diversification of banks into non-interest incomes proves to increase banks’ risk. The objective of this paper is to examine the relationship between banks’ risk and product diversification, in the changing structure of banks in the ASEAN-5 countries. Based on 121 number of commercial, savings and cooperative banks during the period 2002 to 2010, this study displays that banks expanding into non-interest activities generally do not affect banks’ risk but has an impact in decreasing insolvency risk. However, taking into consideration size effects and splitting non-interest activities into both trading activities and commission and fee activities, it is observed that the decrease in insolvency risk is more strongly correlated with commission and fee income than trading activities. Furthermore, it is gathered that the decrease in insolvency risk is more significant in big banks as compared to small ASEAN-5 banks.